Analisis Pemikiran Al-Ghazali Terhadap Permasalahan Fiat Money - Zainol Hasan; Ahmad Faidi Mahrus (Departement of Mathematics Education, 2023)
The role of money in economic activity is as a transaction tool. Al-Ghazali's thought that money should be made of gold and silver. So, it is necessary to conduct an in-depth study of fiat money as a reference or basis for everyone. The method in this research is a literature review that has primary sources from Ihya Ulum Al-Din by Abu Hamid Al-Ghazali and secondary sources from books that examine the concept of fiat maney. Data analysis uses content analysis. Money has no price but can reflect the price of all goods or services. Al-Ghazali's strict prohibitions related to money include hoarding money, counterfeiting currency, and the practice of buying and selling currency. The use of fiat money in Al-Ghazali's thought should be made of gold and silver to avoid usury transactions, because according to him gold and silver are currencies that have stable value. Al-Ghazali strickly rejected the use of fiat money with the reason that currencies other than gold and silver could disrupt the stability of currency values and have an impact on the decline of the country's economy.